A Handbook for Deputy Heads in Schools. - Donnelly, Jim (Routledge, Taylor & Francis Group, 2014)
Aims to provide deputy heads with a practical guide to their complex role in schools. Drawing on his own experience, and mindful of the increasing managerial demands of a more competitive education system, the author offers advice on managing staff, student care, examinations and much more.